The principal representation category of infinite reductive groups is not a highest weight category. Issue 1 (2nd January 2023) - Chen, Xiaoyu
Abstract: This paper shows that the Dong's conjecture in Dong ( J. Algebra 591:342–359, 2022) on the principal representation category of infinite reductive group is not true. Thus, it needs to be modified.